Text, Speech and Dialogue 9th International Conference, TSD 2006, Brno, Czech Republic, September 11-15, 2006, Proceedings - Sojka, Petr; Kopecek, Ivan; Pala, Karel (Lecture Notes in Artificial Intelligence,, 2006)
The annual Text, Speech and Dialogue Conference (TSD), which originated in 1998, is now coming to the end of its ?rst decade. During this time almost 400 authors from 36 countries have contributed to the proceedings. TSD constitutes a recognized forum for the presentation and discussion of state-of-the-art technology and recent achievements in the ?eld of natural language processing. It has become an interdisciplinary forum, interweaving the themes of speech technology and language processing. The conference attracts researchers not only from Central and Eastern Europe but also from other parts of the world. Indeed, one of its goals has always been to bring together NLP researchers with different interests from different parts of the world and to promote their mutual cooperation. This volume containsthe proceedings of the Ninth TSD Conference, held in Brno, Czech Republic in September 2006. Following the review process, 87 papers were accepted out of 175 submitted, an acceptance rate of 49.7%. The number of the submissions this year was the highest so far. We would like to thank all the authors for the efforts they put into their submissions and the members of the Program Committee and reviewers who did a wonderful job helping us to select the most appropriate papers. We are also grateful to the invited speakers for their contribution. Their talks provided insight into important issues, applications and techniques related to the conference topics.